(untitled) (Research, Society and Development, 2022)
The study sought to analyze the social representations of death for health professionals. A systematic literature review was carried out, based on studies cataloged in the BDTD and OASIS portals. The Theory of Social Representations was assumed as a theoretical foundation and the Content Analysis Technique was used to organize and analyze the selected material. Searches were carried out using the keywords: death; Health professionals; social representations. As inclusion criteria, it was admitted: free access texts, from Brazilian studies; that contemplate or touch upon the theme of death/dying/finitude as an object of study; that have health professionals as research subjects and; that are supported by the Theory of Social Representations. Eight works were selected. The results indicate social representations of death as a difficult phenomenon to be experienced and as a passage. They reveal the incipient preparation to deal with death, in health education, constituting practices with a technical emphasis, often stripped of the subjective dimensions of the processes of life and death. It results, therefore, in fragile professional practices regarding terminality, making it difficult to live with this phenomenon. Health professionals seem to resort to a religious cultural repertoire to represent death and dying. Also emerged, associated with the social representation of death, the SR of health professionals as those who save and restore lives. This SR denotes an important interference in the formation of representations of death as difficult to experience.